The Journey Home : Iraqi Invasion of Kuwait and After - Baig, M. A. (Karachi Royal Book Company, 2000)
Include Illustrations, Epilogue and Annexe.
It is a biography.
Keywords: Iraq-Kuwait Crisis (1990-1991) -- Persian Gulf War (1991) -- War victims -- Kuwait -- Atrocities